The Impact of Artificial Intelligence on Auditing Processes and Accuracy: A Future Outlook - Fidyah, Feny; Usman, Susanti; Eki Pradita, Afrila; Mieta Setyawati, Dyah (Dinasti Publisher, 2024)
Artificial Intelligence (AI) is revolutionizing auditing processes, promising significant improvements in accuracy, efficiency, and risk management. This literature review explores the transformative impact of AI on auditing practices and outlines future prospects. AI technologies such as machine learning, natural language processing, and robotic process automation are being integrated into auditing systems, enabling real-time data analysis, anomaly detection, and predictive insights. These advancements not only enhance traditional auditing methodologies but also introduce new approaches capable of handling large volumes of data with unprecedented speed and precision. This article synthesizes current research and industry trends to highlight AI's role in addressing auditing challenges, including fraud detection, compliance monitoring, and audit quality enhancement. Moreover, it examines the implications of AI adoption for auditors, emphasizing the need for upskilling in data analytics and AI technologies. Looking forward, the article discusses potential future developments such as AI-driven continuous auditing, blockchain integration, and ethical considerations in AI-augmented audits.